Politik Hukum Dalam Pembentukan Peraturan Perundang-Undangan Tentang Desa - Mukhamad Luthfan Setiaji (MAGISTRA Law Review, 2026)
The state has explicitly acknowledged the existence of villages and indigenous groups through the Law from past till the present. The most recent revision to the village regulations, Law Number 3 of 2024 concerning the Second revision to Law Number 6 of 2014 concerning Villages, has drawn a lot of attention from many facets of society. The People's Representative Council of the Republic of Indonesia (DPR RI) wants the second amendment draft to Law Number 6 of 2014 concerning Villages to be approved prior to the general election (Pemilu) in 2024, even though the most recent village regulations are not part of the priority National Legislation Program (Prolegnas) for 2023. It is fascinating to examine the legal politics and urgency involved in the creation of Law Number 3 of 2024, which amends Law Number 6 of 2014 about villages in the second place. Normative legal research employing secondary data sources and qualitative descriptive analytical methodologies is the research methodology employed in this work. The study's findings suggest that political factors and the need for quick changes to the legislation do not substantially alter the content of earlier rules.